A simple chemosensor for the dual-channel detection of cyanide in water with high selectivity and sensitivity. Issue 32 (14th March 2016) - Cheng, Xiao-Bin; Li, Hui; Zheng, Feng; Lin, Qi; Yao, Hong; Zhang, You-Ming; Wei, Tai-Bao
Abstract : By a deprotonated mechanism, the simple chemosensorHY showed high sensitivity and selectivity for cyanide in aqueous media. Abstract : We have synthesized a simple chemosensor (HY ) of acylhydrazones and used it for colorimetric detection of cyanide anions (CN − ) in DMSO/H2 O (3 : 7, v/v) mixed solvent. The simple chemosensor displays a specificity response for cyanide over other common anions (F −, Cl −, Br −, I −, AcO −, H2 PO4 −, HSO4 −, ClO4 −, and SCN − ) in mixed solution. Upon treatment with cyanide, HY displayed a remarkable naked-eye and fluorogenic response, simultaneously with significant changes in its UV-visible and fluorescence spectra. Furthermore, competitive anions did not show any significant changes both in colour and emission intensity, indicating the high selectivity of the sensor to CN − . The absorption spectra detection limit of the chemosensor for cyanide was 8.34 × 10 −7 M and the fluorescence spectra detection limit was 2.85 × 10 −8 M. The cyanide test strips based on the chemosensor could serve as a convenient cyanide test kit. Furthermore, the chemosensor was successfully applied to the detection of cyanide in sprouting potatoes.